Aids prevention in an odontologic clinic setting: knowledge levei of dentists in a region of São Paulo state, Brazil - Pereira, Antonio Carlos; Temporini, Edméa Rita (Brazilian Journal of Sexually Transmitted Diseases, 1999)
Identifying knowledge regarding Aids Acquired Immunodeficiency Syndrome) prevention in a dental office among dentists working at São Paulo city, State of São Paulo, Brazil, were the main goals of this study, in arder to carry it out, 150 dentists integrated the designed sample using a structured ques-tionary based on a exploratory study. Results were as follows: the dentists demonstrated knowledge concerning Aids prevention and HIV inativation. The majority of the respondents mentionated the efficacy of dry heat (96,7%) and humidy heat (98,6%) in the HIV inativation in a dental office; almost 100,0% of them demonstrated knowledge concerning in a necessity of the sterilization of clinicals, surgicals and periodontals instruments. The respondents were in doubt about the necessity of the sterilization of orthodontics instruments, needles and surgi cal knives and they didn ’t believe in the necessity about one way needles (33,3%) and one way surgical knives (20,0%). The major source ofinformation about Aids was the periodic.